POTENTIAL OF MORINGA LEAF EXTRACT GEL (Moringa oleifera Lam.) AS AN ANTIBACTERIAL AGAINST Staphylococcus aureus CAUSES OF ACNE - Asiska Permata Dewi; Alfin Surya; Fahma Shufyani (JURNAL KATALISATOR, 2026)
Moringa leaves (Moringa oleifera Lam.) can be utilized by the community to heal wounds, beriberi, and fever; have anti-inflammatory and analgesic properties; and treat skin disorders caused by bacteria. One of the skin diseases is acne, which is caused by the bacterium Staphylococcus aureus. The aim of this study is to determine the antibacterial activity of a gel made from moringa leaf extract against Staphylococcus aureus and to identify the secondary metabolite compounds of the extract through phytochemical screening. This research is a laboratory experiment that involves creating moringa leaf extract gel at concentrations of 2%, 4%, 6%, and 8% to inhibit the growth of Staphylococcus aureus. Antibacterial testing was conducted using the well diffusion and disc diffusion methods and analyzed using one-way ANOVA. Based on the results of the phytochemical screening, the extract contains flavonoid, alkaloid, saponin, tannin, and terpenoid compounds. The results of the study showed that the antibacterial activity of the gel with the well method at concentrations of 2%, 4%, 6% and 8% obtained an average inhibition zone of 7.68 mm; 8.8 mm; 9.18 mm; 9.55 mm. While with the well method, the average inhibition zone at concentrations of 2%, 4%, 6% and 8% was 8.55 mm; 9.03 mm; 9.17 mm; 9.88 mm. The ANOVA test analysis obtained a result of p = 0.000 smaller than α = 0.05 which means there is a significant difference in the average diameter of the inhibition zone between the treatment groups.